Evaluation of growth and carcass performance of crossbred F1 between wild boar from Central Highland with Mong Cai and Soc pigs - Nghia Son, Hoang; Thanh Long, Le (Vietnam Journal of Biotechnology, 2020)
This study aimed to evaluate the growth and meat productivity of F1 crossbreds between Central Highland wild boards with Mong Cai and Soc pigs. The experiment was conducted on 2 groups of F1 pigs including F1 crossbred between native wild boars and Mong Cai pigs (RxM), F1 crossbred between of native wild boars and Soc (RxS) pigs, and 2 groups of Mong Cai pigs (M) and Soc pigs (S). The results demonstrated that the growth of F1 pig of RxM group was higher than RxS group after 3 months and 8 months of breeding. The carcass analysis showed that there was no difference in the slaughter weight of pigs between the RxM and M groups, as well as between the RxS and S groups. Pigs from the S group showed the lowest hanging weight (17.60 ± 0.52 kg) and lowest dressed weight (14.92 ± 0.49 kg) among the groups. There was no difference in the hanging weight and dressed weight among the RxM and M groups. However, the ratio of hanging weight (75.95 ± 0.23%) and dressed weight ratio (65.00 ± 0.18%) of RxM group is higher than M group (72.53 ± 0.44% and 62.24 ± 0.51%, respectively). The RxS group also had a higher percentage of hanging weight (74.28 ± 0.57%) and dressed weight (63.73 ± 0.48%) than the S group (71.10 ± 0.40% and 60.25 ± 0.50%, respectively). In this study, we also found that F1 hybrid pigs exhibited a lower backfat thickness than the M and S groups. In contrast, the backskin thickness increased in F1 hybrid groups. The above results showed that the hybridization of with Mong Cai and Soc pigs with Central Highland wild boars could improve the meat productivity of their F1 generation.